HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN PELAKSANAAN IMUNISASI MEASLES RUBELLA DI RT 05 KELURAHAN TAGARAJA KECAMATAN KATEMAN KEBUPATEN INDRAGIRI HILIR TAHUN 2018 - Suhartini Suhartini (Universitas Prima Indonesia, 2019)
Immunization is the giving of immunity to infants and children to various diseases, so that babies and children grow in healthy condition. Provision of immunization is a preventive measure so that the body is not infected with certain infectious diseases such as tetanus, whooping cough (pertussus), measles (measles), polio and tuberculosis or if there is any, does not have a fatal effect on the body. Therefore researchers are interested in examining the relationship between knowledge and attitudes of mothers with the implementation of MR immunization in Rt 05 Kelurahan Tagaraja Kecamatan Kateman Kebupaten Indragiri Hilir Tahun 2018. This study uses a cross sectional research design. The population of this study were all mothers with immunization in RT 05 Tagaraja Village, Indragiri Hilir District Kateman District in 2018, 48 people and a sample of 48 people, with total sampling technique. Data analysis techniques were performed using chi-square statistical test analysis. The results of the study showed that there was a significant relationship between the relationship of knowledge and attitudes of mothers with the implementation of immunization of rubella measles (MR)in RT 05 Kelurahan Tagaraja Kecamatan Kateman Kabupaten Indragiri Hilir Tahun 2018 with p value 0,002 (p < 0,05. Based on the results of this study it can be concluded that there is a relationship between knowledge and attitudes of mothers with the implementation of immunization of rubella measles (MR)in RT 05 Kelurahan Tagaraja Kecamatan Kateman Kabupaten Indragiri Hilir Tahun 2018. Suggestions for mothers It is hoped that for the research location to make an extension program before the scheduled implementation of the rubella measles immunization to provide education on maternal health and government programs in the implementation of immunization for rubella measles (MR) can be carried out.